2004
DOI: 10.1117/12.540305
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on fuzzy skyhook control of a vehicle suspension system using a magnetorheological fluid damper

Abstract: Skyhook control is an effective control strategy for suppressing vehicle vibration. It is typically classified as onoff skyhook control and continuous skyhook control. In this study, a fuzzy skyhook control is proposed. It combines the fuzzy logic theory with the skyhook principle to improve control performance. In order to compare performance of each control strategy, an experimental study is prepared utilizing a quarter car model of highmobility multi-purpose wheeled vehicle (HMMWV) with a controllable magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In the case of the Fuzzy controller, the outcome (Equation (13) or (14)) is a simple continuous representation of the original Skyhook control strategy with a few lines of code that is simply embedded in a low-cost micro controller. By tuning the membership function parameters (see Equations (4) and (5)), sensitivity and smoothness of the Fuzzy Skyhook controller can also be altered and adjusted. q changes the membership function growth or decay rate.…”
Section: Fuzzy Network Model Of Skyhookmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the Fuzzy controller, the outcome (Equation (13) or (14)) is a simple continuous representation of the original Skyhook control strategy with a few lines of code that is simply embedded in a low-cost micro controller. By tuning the membership function parameters (see Equations (4) and (5)), sensitivity and smoothness of the Fuzzy Skyhook controller can also be altered and adjusted. q changes the membership function growth or decay rate.…”
Section: Fuzzy Network Model Of Skyhookmentioning
confidence: 99%
“…Then, develop the vehicle's vertical model state-space realisation (see Equation (2)), accordingly. (3) Determine and adjust the parameters of the input Fuzzy sets (see Equations (4) and (5)). …”
Section: Fuzzy Network Model Of Skyhookmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al showed that the control performance of semi-active suspension system could be better than on-off control when proper fuzzy logic which depicts the skyhook algorithm is used [9], [10].…”
Section: A Fuzzy Skyhook Controlmentioning
confidence: 99%
“…A fail-safe MRF damper is utilized for vibration suppression of the HMMWV suspension [10][11][12][13]. The fail-safe MRF damper can produce a damping force nearly the same as an OEM damper at its off state (zero electric input current) and provide sizable dynamic force range to allow controllability (with the supply of electrical current).…”
Section: Introductionmentioning
confidence: 99%